ANALISIS PERAMALAN PENJUALAN KERIPIK SINGKONG DI UKM TIGA SERANGKAI BATAM - fauzi, gusvi abnan; Arista, Anggia (Computer Science and Industrial Engineering, 2021)
Small and medium-sized enterprises (SMEs) that are currently developing the most are food, beverage, and furniture SMEs. One of these SMEs is the Tiga Serangkai UKM which is engaged in the production of cassava-based crispy snacks located in the city of Batam and started operating in 2005. Unfortunately, from several outlets owned by SME Tiga Serangkai, the outlets in the Mall and Port experienced a decline. which is quite significant. Tiga Serangkai SMEs have not yet found the right method or way to estimate the number of consumer needs in the future. Seeing the problems faced by SME Tiga Serangkai related to sales forecasting, researchers are interested in further researching related to forecasting sales of cassava chips using Exponential smoothing and Moving Average methods. This research is a descriptive research with a qualitative approach through literature study. The sample was selected by purposive sampling method. The sample selected is sales data at SME Tiga Serangkai Outlet Mall and Port from June 2020 to May 2021. The data obtained is then analyzed using the Moving Average and Exponential Smoothing methods. As a result, the correct sales forecast for the next 6 months for both outlets is the exponential smoothing method with = 0.9.